MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI PERMAINAN PUZZLE PADA ANAK USIA DINI - Rima (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2024)
This research aims to improve fine motor skills in Kasih Ibu PAUD children. The subjects in this research were 15 class A students. Where the researcher made initial observations on the 15 students. The research procedure uses Classroom Action Research , the researcher collects data by observation and documentation. The results obtained from the first cycle test are 53%, including in the incomplete value category, while the second cycle test results are 80%, including in the complete value category. So it can be concluded that using the Puzzle playing method can improve children's fine motor skills very well.